JOB ROTATION ON EMPLOYEE MOTIVATION IN PT. PERTAMINA (PERSERO) MANADO - Palulungan, Josep; Saerang, David P. E.; Tielung, Maria (Universitas Sam Ratulangi, 2014)
The practice of job rotation is already become an improving factor to the skills and abilities of the employees. Social, cultural and belief sometimes affect the transfer of understanding in practicing job rotation. In the end, this job rotation policy sometimes affect motivation of employee that resulted in their performance. Besides, this practice sometimes affect the motivation because this practice will make employee should adapt with a new work condition and environment. This element then could affect the motivation of employee in conduction job rotation. The objective of this study is to analyze job rotation effect on employee motivation in PT. Pertamina (Persero). There are several facts that become consideration or reason to conduct this research which are: (1) there are a lot of variation in employees based on their work duration and quantity of job rotation. (2) There are some employees that work not based on their academic background or their work experience. (3) Employees in Marketing Branch Office Manado come from some different places around Indonesia. The population observed is Pertamina’s employee who already performed job rotation as many as 10 respondents. The results based on data collection method processed using the In-Depth Interview. There are four major effects of job rotation which are (1) employee be more discipline, responsible and perform the best. (2) Employee gain new experience. (3) Job rotation improve skills and abilities. (4) Job rotation improve employee’s position in the company. But the company must conduct interview with the employee, create a forced location rotation, and monitoring employee’s job description. Keywords: human resource management, job rotation, motivation